Feasibility of a Kinect®-based rehabilitation strategy after burn injury. Issue 8 (December 2018) - Pham, Tam N.; Wong, Joshua N.; Terken, Tonya; Gibran, Nicole S.; Carrougher, Gretchen J.; Bunnell, Aaron
Highlights: Jintronix software is a new avenue for technology-assisted rehabilitation in burn patients. This feasibility study demonstrates a positive reaction and an acceptable level of safety. These results helped design a prospective randomized trial of home-based rehabilitation. Abstract: Introduction: The advent of consoles that deliver both interactive games and therapy may augment rehabilitation options in burn patients. The Jintronix software combines therapy-specific software and interactive gaming as a form of coaching and records patient performance on the Kinect ® platform. Our objective was to determine the feasibility of a set of Jintronix games and therapy modules in hospitalized adult burn patients. Methods: We conducted a prospective single center feasibility study from August through October 2016. The study enrolled subjects to conduct 1 supervised session with 6 Jintronix modules targeting their burned areas of the body, with an acceptability survey and a safety analysis. We also performed qualitative analysis to detect major themes from free-text responses. Results: We enrolled 20 participants. Eleven (55%) completed all the modules; reasons for incompletion included baseline shoulder abduction pain and poor balance. Participants responded that the activity was comfortable (90%), safe (100%), easy to understand (95%), and improved strength/range of motion (100%). Mean module completion time was 43 ± 10 min. Mean pain score was 3.8 ± 2.8 (out of 10) and localized to burned areas. The wall climbing module had 4 episodes of temporary imbalance. Eight (40%) participants recorded fatigue at completion and noted "sweating" or "feeling stretched". Qualitative analysis highlighted that the activity was "fun/cool" and a "good challenge". Negative themes included "inaccurate depth" sensing and "too lengthy" on a specific module. Conclusions: A Jintronix-based therapy demonstrated good acceptability and safety in hospitalized burn patients. Feedback from this study led to software modifications implemented by the Jintronix company. This feasibility study has informed the design of a prospective randomized controlled trial to determine whether a virtual-environment home rehabilitation strategy improves functional outcomes after burn injury.